Dual-Targeting and Stimuli-Triggered Liposomal Drug Delivery in Cancer Treatment - AlSawaftah, Nour Majdi (2021)
The delivery of chemotherapeutics to solid tumors using smart drug delivery systems (SDDSs) takes advantage of the unique physiology of tumors (i.e., disordered structure, leaky vasculature, abnormal extracellular matrix (ECM), and limited lymphatic drainage) to deliver anti-cancer drugs with reduced systemic side effects. Liposomes are the most promising of such SDDSs and have been well investigated for cancer therapy. To improve the specificity, bioavailability and anti-cancer efficacy of liposomes at the diseased sites, other strategies such as targeting ligands and stimulus-sensitive liposomes have been developed. This review highlights relevant surface functionalization techniques and stimuli-mediated drug release for enhanced delivery of anti-cancer agents at tumor sites, with a special focus on dual functionalization and design of multi-stimuli responsive liposomes.